ISLAMIC EDUCATION MANAGEMENT: INTEGRATION OF HOLISTIC APPROACHES IN FORMAL AND NON-FORMAL EDUCATION - Nuryahman, Muhammad; Majeed, Muhammad Kashif; Zulaiha, Dewi (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
Every educational institution requires effective management in its operations. Good management ensures that the institution achieves success and is capable of delivering optimal educational quality. This study discusses factors that affect the implementation of Islamic Education management across various educational levels, particularly in both formal and non-formal education. The research employs a qualitative approach by combining various methodologies and data sources to provide a deeper understanding of Islamic Education management, utilizing descriptive analysis. The findings indicate several factors that influence the success of Islamic Education management, including leadership, human resources (HR), infrastructure, curriculum, and stakeholders. Meanwhile, non-formal education plays a significant role in the overall education system, particularly in meeting the needs of communities that are not reached by formal education. Formal and non-formal education complement each other in shaping competent and qualified individuals. Although both differ in structure, curriculum, and implementation methods, they share the same goal: to enhance the potential of individuals and society.  Keywords: Islamic Education Management; Holistic Approach; Formal Education; Non-formal Education; Qualitative Research.   Abstrak Setiap lembaga pendidikan memerlukan manajemen yang efektif dalam operasionalnya. Manajemen yang baik akan menjamin keberhasilan lembaga dan mampu memberikan mutu pendidikan yang optimal. Penelitian ini membahas faktor-faktor yang mempengaruhi penerapan manajemen Pendidikan Islam di berbagai jenjang pendidikan, khususnya pada pendidikan formal dan nonformal. Penelitian ini menggunakan pendekatan kualitatif dengan menggabungkan berbagai metodologi dan sumber data untuk memberikan pemahaman yang lebih mendalam tentang manajemen Pendidikan Islam, dengan menggunakan analisis deskriptif. Hasil penelitian menunjukkan beberapa faktor yang mempengaruhi keberhasilan manajemen Pendidikan Islam, antara lain kepemimpinan, sumber daya manusia (SDM), sarana prasarana, kurikulum, dan pemangku kepentingan. Sementara itu, pendidikan nonformal memegang peranan penting dalam sistem pendidikan secara keseluruhan, khususnya dalam memenuhi kebutuhan masyarakat yang tidak terjangkau oleh pendidikan formal. Pendidikan formal dan nonformal saling melengkapi dalam membentuk individu yang kompeten dan berkualitas. Meskipun keduanya berbeda dalam struktur, kurikulum, dan metode pelaksanaan, keduanya memiliki tujuan yang sama, yaitu meningkatkan potensi individu dan masyarakat. Kata Kunci: Manajemen Pendidikan Islam; Pendekatan Holistik; Pendidikan Formal; Pendidikan Nonformal; Penelitian Kualitatif.